2019
DOI: 10.52118/edumasda.v3i2.40
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Stres Dengan Kualitas Tidur Pada Mahasiswa Tingkat Akhir

Abstract: Mahasiswa merupakan salah satu kelompok dewasa awal yang memiliki banyak aktivitas, sehingga mahasiswa menjadi kelompok yang berisiko memiliki kualitas tidur yang buruk. Salah satu penyebab kualitas tidur yang buruk yaitu faktor stres. Penelitian ini dilakukan untuk mengidentifikasi hubungan stres dengan kualitas tidur pada mahasiswa tingkat akhir di STIKes Kharisma Persada. Penelitian ini menggunakan jenis penelitian observasional analitik dengan pendekatan kuantitatif dan desain cross sectional. Populasi dal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 0 publications
1
3
0
2
Order By: Relevance
“…Several studies that have proven that stress plays a role in the quality of a person's sleep were found by Noveni et al (6), which state that stress, especially academic stress, has a role in the quality of student sleep. Other findings also state that there is a correlation between stress and sleep quality in the final year (28). These findings confirm that stress, both general and specific stress, has a role in the quality of one's sleep.…”
Section: Discussionsupporting
confidence: 59%
“…Several studies that have proven that stress plays a role in the quality of a person's sleep were found by Noveni et al (6), which state that stress, especially academic stress, has a role in the quality of student sleep. Other findings also state that there is a correlation between stress and sleep quality in the final year (28). These findings confirm that stress, both general and specific stress, has a role in the quality of one's sleep.…”
Section: Discussionsupporting
confidence: 59%
“…As shown by Chi-square analysis P value = 0,047, there is a significant relationship between stress and sleep disorder in student Faculty of Medicine USU. The same studies by Ratnaningtyas and Fitriani at The Universitas Sumatera Utara (2019) reported a significant relationship between stress and quality of sleep in students (P Value=0,016) [10].…”
Section: Stress Can Have Implications On Physiological Mechanisms Of ...mentioning
confidence: 73%
“…Hasil penelitian terdahulu pada mahasiswa tingkat akhir di STIKES Kharisma Persada Tangerang Selatan yang diuji menggunakan uji chi-square didapatkan nilai p value 0,016. Artinya terdapat hubungan antara kualitas tidur dan stres (12).…”
Section: Pendahuluanunclassified
“…Hasil penelitian menunjukkan adanya perbedaan tingkat stres jika dilihat dari umur. Sebaliknya, tidur yang cukup secara konsisten berkaitan dengan peningkatan kesehatan emosional (12). Durasi tidur yang pendek di malam hari berhubungan dengan berkurangnya mood dan meningkatkan kecemasan pada individu (19).…”
Section: Hubungan Umur Dan Tingkat Stres Respondenunclassified